Sprint acceleration mechanical profiling for the NFL draft - Delaney, J. A.; Olson, T. M.; Morin, J.-B. (Sport Performance & Science Reports, 2018)
The NFL Scouting Combine is a weeklong event where a group of high-performing graduating collegiate American football (AF) athletes are invited to a central location to undergo a series of physical, psychological and technical evalu ations. Running speed and acceleration abilities are critical capacities for performance in AF, and therefore the 40-yard (36.6 m) dash represents one of the most important physi cal tests. It may be that performance in this particular test, and the underlying mechanical determinants, are related to achieving the goal of being drafted into the NFL. This study aimed to rstly describe the sprint acceleration mechanical pro le of athletes participating in the NFL Scouting Combine, and to secondly ascertain which biomechanical variables are associated with selection in the NFL draft.